Improving the Bending Quality of SUS 201 1B Material by Optimization of the Processing Parameters using Taguchi Method - Pramudya, Axel Satya; Nugraha, Aditya (Universitas Muhammadiyah Yogyakarta, 2024)
Sheet metal bending was a type of sheet metal forming process that produced sheet metal bending according to a certain angle and length using a die. The formed process caused elastic and plastic deformation, resulting in springback and sheet metal elongation. The research analysed used the Taguchi method to find the best arrangement of bending parameters that produced the best bending angle and side length. The bending parameters selected in the study were material cutting orientation factor, punch velocity, and holding time. The ANOVA method would follow the tested results to determine the contribution of each parameter tested. The results stated that the material cutting orientation 0-degree, punched velocity of 10 mm/s, and holding time of 5 seconds was the best parameter arrangement that produced the best bending angle with the smallest springback angle. The bending parameter arrangement for the best-bending side length was a material cutting orientation of 0 degrees, pressing speed of 15 mm/s, and holding time of 5 sec, it minimize springback, significantly optimizing the deformation process for SUS 201 1B materials. The studied results concluded that the material cutting orientation factor had the largest contribution to the angle and length of the bending side, with a percentage contribution of 98.105% and 98.499%.